Electrospinning of aligned fibers with adjustable orientation using auxiliary electrodes - Arras, Matthias M L (Sci Technol Adv Mater, 2012)
A conventional electrospinning setup was upgraded by two turnable plate-like auxiliary high-voltage electrodes that allowed aligned fiber deposition in adjustable directions. Fiber morphology was analyzed by scanning electron microscopy and attenuated total reflection Fourier transform infrared spectroscopy (FTIR-ATR). The auxiliary electric field constrained the jet bending instability and the fiber deposition became controllable. At target speeds of 0.9 m s(−1) 90% of the fibers had aligned within 2°, whereas the angular spread was 70° without the use of auxiliary electrodes. It was even possible to orient fibers perpendicular to the rotational direction of the target. The fiber diameter became smaller and its distribution narrower, while according to the FTIR-ATR measurement the molecular orientation of the polymer was unaltered. This study comprehensively documents the feasibility of directed fiber deposition and offers an easy upgrade to existing electrospinning setups.